2014
DOI: 10.1016/j.ecolind.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Long term variation of an amphipod species’ population secondary production as indicator of incomplete resilience in a temperate estuary

Abstract: a b s t r a c tDuring the last decades many estuaries underwent ranges of environmental pressure due to increasing anthropogenic pressures and the undertaken of mitigation measures to prevent the impoverishment of these areas. The Mondego estuary (NW Atlantic coast of Portugal), a mesotidal shallow estuary, is one typical case of this. In the 1980s, the system was characterized by rich and stable animal and vegetal communities, with no eutrophication symptoms (pre-eutrophication period), whereas during the 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…Both organisms used in this study are resilient inter‐tidal species (Milton, ), the temperature ranges for E. marinus are from 5·4–31·7° C (Leite et al., ), which is far higher than the 17·5° C recorded optimal temperature for the northerly distributed L. pholis (Horn & Gibson, ; Francisco et al., ). Davenport & Vahl () experimentally identified 16° C as the peak temperature for consumption of seaweed in L. pholis .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Both organisms used in this study are resilient inter‐tidal species (Milton, ), the temperature ranges for E. marinus are from 5·4–31·7° C (Leite et al., ), which is far higher than the 17·5° C recorded optimal temperature for the northerly distributed L. pholis (Horn & Gibson, ; Francisco et al., ). Davenport & Vahl () experimentally identified 16° C as the peak temperature for consumption of seaweed in L. pholis .…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, E. marinus is an effective indicator species due to its prevalence, susceptibility to abiotic perturbation 152 J . S O U T H E T A L. and its importance as a prey species to higher trophic levels (Múrias et al, 1996;Leite et al, 2014). Echinogammarus marinus is an important prey species of L. pholis and other marine intertidal species; thus, it is a sympatric species and therefore will experience the same perturbations to environment as L. pholis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated predation by juvenile Scyliorhinus canicula (lesser-spotted dogfish) on amphipod prey Echinogammarus marinus. Both species are ubiquitous in temperate waters (Ellis and Shackley 1997;Duffy and Harvilicz 2001), resilient (Múrias et al 1996;Revill et al 2005;Leite et al 2014) and pliable laboratory species (Sims 2003). These are ecologically relevant species as E. marinus has large impacts upon community structuring (Duffy and Hay 2000;Dick et al 2005), and is an important prey species (Leite et al 2014) that can additionally be considered a proxy for other small crustacean species and small fish due to strong swimming behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Both species are ubiquitous in temperate waters (Ellis and Shackley 1997;Duffy and Harvilicz 2001), resilient (Múrias et al 1996;Revill et al 2005;Leite et al 2014) and pliable laboratory species (Sims 2003). These are ecologically relevant species as E. marinus has large impacts upon community structuring (Duffy and Hay 2000;Dick et al 2005), and is an important prey species (Leite et al 2014) that can additionally be considered a proxy for other small crustacean species and small fish due to strong swimming behaviours. S. canicula is a generalist benthic predator (Kaiser and Spencer 1994;Domi et al 2005) with high abundances (Genner et al 2010;Sguotti et al 2016) that have been found to increase with increasing temperature (Sguotti et al 2016).…”
Section: Introductionmentioning
confidence: 99%